Teaching Homeopathy in U.S. Pharmacy Schools - Esra'a Khader; William Doucette (University of Minnesota Libraries Publishing, 2024)
Objectives: Pharmacists often advise patients on the use of over-the counter (OTC) medications. Such a class of medications that is growing in popularity is homeopathic products. Little is known about student pharmacists are being educated about homeopathy. The objectives of this study were to describe homeopathic topics being taught in pharmacy schools and to evaluate faculty views about pharmacists' roles in counseling patients about homeopathic products.   Method: A mixed method design collected information about teaching homeopathy in US pharmacy schools. Online surveys were distributed to 3,300 pharmacy practice faculty members representing all schools accredited in the US. Frequencies were calculated to describe faculty characteristics and their responses. Moreover, 18 interviews of faculty involved with teaching homeopathy were conducted to learn about homeopathy teaching and expectations about roles of pharmacists in counseling patients. Results: Survey data were collected from 365 respondents, with 51.2% of the respondents teaching in public universities, 49.6% having PGY1 training and 35.8% being associate professors. Over half (84 of 137) of the responding schools of pharmacy reported teaching homeopathy to pharmacy students. In addition, most interviewed faculty emphasized that pharmacists should be knowledgeable and able to counsel patients effectively on homeopathic products. Conclusion: Over half of schools of pharmacy are teaching students about homeopathy topics. Further, there was support for pharmacists being able to counsel effectively about homeopathic products.